Exponential stability for magneto-micropolar fluids. (September 2016) - Braz e Silva, P.; Friz, L.; Rojas-Medar, M.A.
Abstract: We prove existence, uniqueness and exponential stability of mildly decaying global strong solutions for the magneto-micropolar fluids system in three space dimensions. Our main objective is to study the convergence of nonstationary solutions to stationary solutions for the system fluids when t → ∞ . We show that under mild suitable conditions the convergence is indeed exponential.